Teaching flamenco zapateado: a new notation-based methodology - de las Heras Fernández, Rosa (ARTSEDUCA, 2021)
Dance has traditionally been taught using a style based on teacher-pupil oral transmission, imitation and repetition. While there are notation methods for dance, few proposals for zapateado notation exist. This research develops a critical analysis not only of the currently existing notation systems for flamenco zapateado, but also of rhythmic notation systems for percussion based on the traditional Western system of musical notation, which form the basis of the foundations of the system of the method of notation presented here. The article shows that this flamenco zapateado notation system is the first to combine how the foot strikes the floor with the rhythmic aspects using notation with a clear visual appearance and a sequence of didactic content which takes into account motor aspects as well as rhythmic ones. This research is linked to the Research Project A connected classroom. The teaching portfolio as a narrative-artistic resource of research and learning, in the training of teachers of Primary Education (2019-2020), in the First Plan of Research and Transfer of the University of Malaga.
Keywords: teaching; dance; notation; zapateado; flamenco; Emerging; Scopus